A comparative study on students' performance in entrepreneurial education using Face-To-Face and Online Distance Learning (ODL) instructional approaches / Nazlin Emieza Ngah ... [et al.] - Ngah, Nazlin Emieza; Shamsudin, Azlina; Abdol Ghapar, Marha; Ibrahim, Norlaila; Ismail, Rusnah; Johar, Norchahaya (Universiti Teknologi MARA, Perlis, 2021)
Malaysia's Ministry of Higher Education announced in early March 2020 that all universities' teaching and learning (TL) processes must be conducted entirely online until the end of the year to prevent Covid-19 from spreading. This change has drastically altered the way teachers teach and students learn, and as a result, the impact on both lecturers and students has been enormous. This study aimed to compare students' performance in the Fundamentals of Entrepreneurship (ENT300) subject at Universiti Teknologi MARA (UiTM) Cawangan Terengganu when using an online learning approach as against a traditional face-to-face approach. Many scholars agreed that the face-to-face approach is more effective and gives students more fulfilment than the online method because students prefer to see and hold paper-based reading material and the satisfaction derived from experiencing the lessons live. This descriptive study data were taken from two different learning approaches, face-to-face and online distance learning (ODL) classes, and the results showed that students' performance is better when lessons are conducted face to face proving that the difference in teaching and learning approach affects the students' grades.